FILM AS AN EDUCATIONAL MEDIA IN BUILDING AWARENESS ON WILD ANIMAL CONSERVATION (CASE STUDY: PETUALANGAN SHERINA 2) - Setiaji, Gumelar; Altamira, Melisa Bunga (UI Scholars Hub, 2024)
Currently, films are not only a medium for entertainment, but can also be used as a medium for information, persuasion, and even education. Nature conservation is one of the environmental issues that is currently of concern. In a survey conducted by a non-governmental organization, the public paid sufficient attention to protecting biodiversity, flora, and fauna. Wild animal conservation is an issue that will be addressed in this research. The film